The Challenge of Multi Drug Resistant Bacteria in Intensive Care Patient Management in Bangladesh - Banik, Debabrata; Banik, Shibani; Mondal, Montosh Kumar (Journal of the Bangladesh Society of Anaesthesiologists, 2016)
Abstract not available Journal of Bangladesh Society of Anaesthesiologists 2014; 27(1): 24-26